Study on the Interaction between Soil and the Five-Claw Combination of a Mole Using the Discrete Element Method - Yuwan Yang; Mo Li; Jin Tong; Yunhai Ma (Applied Bionics and Biomechanics)
A mole is a born digger spending its entire existence digging tunnels. The five claws of a mole’s hand are combinative to cut soil powerfully and efficiently. However, little was known in detail about the interaction between the soil and the five-claw combination. In this study, we simulated the soil cutting process of the five-claw combination using the discrete element method (DEM) as an attempt for the potential design of soil-engaging tools to reduce soil resistance. The five-claw combination moved horizontally in the soil bin. Soil forces (draught and vertical forces) and soil failure (soil rupture distance ratio) were measured at different rake angles and speeds. Results showed that the draught and vertical forces varied nonlinearly as the rake angle increased from 10 to 90°, and both changed linearly with the speed increasing from 1 to 5 m/s. The curve of the soil rupture distance ratio with rake angles could be better described using a quadric function, but the speed had little effect on the soil rupture distance ratio. Notably, the soil rupture distance ratio of the five-claw combination in simulation was on average 19.6% lower than the predicted ratio of simple blades at different rake angles indicating that the five-claw combination could make less soil failure and thereby produce lower soil resistance. Given the draught and vertical forces, the performance of the five-claw combination was optimized at the rake angle of 30°.